Cold Storage of Two Selections of Soursop (Annona muricata L.) in Nayarit, Mexico - José Orlando Jiménez-Zurita; Rosendo Balois-Morales; Irán Alia-Tejacal; Leticia Mónica Sánchez Herrera; Edgar Iván Jiménez-Ruiz; Juan Esteban Bello-Lara; Juan Diego García-Paredes; Porfirio Juárez-López (Journal of Food Quality)
The maturity of two selections of soursop (G1 and G2) from Nayarit, Mexico, was evaluated under environmental conditions at 22°C and refrigeration at 15°C stored for 6 and 8 days, respectively. Maximum CO2 and ethylene values were present on the fifth and sixth day. The fruits exposed at 15°C had a significantly lower weight loss (5%) and showed no chilling injury. The firmness of two selections decreased more than 90%. The concentration of TSS increased to 5.3 to 15°Brix, and the titratable acidity was higher for fruit stored at 22°C. The highest concentration of phenols was recorded on the fourth day of storage at 22°C. The enzymatic activity of PPO was increased from physiological ripening to consumption ripening for both treatments. The two selections stored at 22°C registered the highest level of PME activity at ripeness. Shelf life was increased by up to 8 days (4 days at 15°C plus 4 days at 22°C) without causing chilling injury or alterations in the ripening process of the fruits. No significant differences were observed between the two selections evaluated; postharvest handling was considered to be similar; however, it would be advisable to evaluate other technologies combined with refrigeration.